Influences on Grief among Parentally Bereaved Adults. (October 2014) - Carver, Kellye S.; Hayslip, Bert; Gilley, Angela; Watts, Justin
Although the parent-child relationship is significant throughout life, many changes occur as children grow, particularly during young adulthood. Parental loss and resulting grief during adulthood is likely influenced by many variables, including age, gender, relationship quality, and sex roles. In the present study, parentally bereaved adults completed measures assessing parental involvement, personal grief and adjustment, and sex role preferences. Analyses of covariance indicated that gender of the bereaved child was significant in predicting some aspects of grief, wherein females were more strongly impacted by the loss of a parent, irrespective of that parent's sex. However, the interaction of sex of parent and sex of child was also significant, suggesting that maternal loss may be particularly difficult for daughters. Results suggested that women may have a stronger emotional experience of grief and maintain closer bonds with a deceased mother. This may result from deeper emotional connections, feeling excluded by age peers, or vulnerability for rumination.